PERANCANGAN PROTOTYPE ROBOTIK MOBIL PEMILAH SAMPAH OTOMATIS DENGAN PENGGUNAAN BLUETOOTH BERBASIS ARDUINO UNO - Sudarmaji, Sudarmaji; Irawan, Dedi (Jurnal Mahasiswa Ilmu Komputer, 2023)
The concept behind this research is the development of an automatic control system, a vehicle that can be operated without a crew and controlled remotely by using Bluetooth as a controller connection. Robotic Prototype Garbage sorting car is a robot construction that has an actuator in the form of wheels to move and move positions from one point to another. Robotic Prototype This garbage sorting car is designed to move using Arduino Uno with a Bluetooth connection controller that has applications that are suitable for robot movement through Android smartphone control. This Robotic prototype uses Arduino Uno as a Bluetooth robot control system, the module for the tool made this time uses a Bluetooth module as a data receiver that is sent via an android smartphone which will then be processed by Arduino and then forwarded to the MG90S motor driver which will provide output to move the DC motor according to commands given wirelessly. The method used is an experimental method, the research carried out will focus on communication between the connecting device and the Arduino Uno via Bluetooth to control the Robotic Prototype device. In its implementation, it can be applied to reach locations that are difficult or dangerous enough for humans to enter, so that with technology like this it will make it easier for humans to reach these areas without having to enter the location but only by controlling the device remotely.